Efficacy comparison of Kirschner-wire tension band and anchor loop plate in treatment of olecranon fracture - Du, Bing; Su, Yu; Ma, Teng; Ji, Shuai; Lu, Yao; Zhang, Kun; Li, Zhong; Li, Ming (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: This study aimed to introduce a new surgical method for the fixation of olecranon fractures, and to compare the biomechanical stabilit y and clinical efficacy of Kirschner wire tension band and anchor loop pla te ( ALP ) in the treatment of olecranon fractures.: A finite element model was established to analyze the mecha nical properties of Kirschner wire tension and anchor loop plate fixation f or olecranon fracture. The clinical data of 53 patients with olecranon fract ures admitted to our hospital from March 2016 to October 2021 were retr ospectively analyzed. Among them, 22 cases were fixed with an anchor l oop plate ( ALP group ), and 31 patients were fixed with the Kirschner wi re tension band technique. By reviewing the medical records and followup results, the final elbow mobility, secondary surgery, postoperative com plications and elbow function recovery Mayo score and DASH score wer e compared between the two groups.Results：The biomechanical analysis of the finite element model showed that under the load of 120 N, the maximum displacement of the Kirschner wire group was 1.09 times that of the ALP group, the maximum stress of the Kirschner wire group was 1.33 times that of the ALP group, and the maximum stress of the olecranon proximal bone of the Kirschner wire group was 2.17 times that of the ALP group.